Unmasking the Tape of Electoral Fraud in Grassroots Nigeria: Evidence from the Management of the Local Council Elections by the State Independent Electoral Commissions (SIECs) - Umar Deribe , Abacha; Sambo , Usman; Sule , Babayo; Salihu, Ibrahim (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Electoral fraud is identified as an albatross on genuine democratization in Nigerian politics. The Nigerian political culture demonstrates a zero-sum game where a winner takes all and where a winner employs all amoral ineptitude to secure victory. The situation is escalated at the grassroots level in the country where the constitutional three-tier of the federal, state and local system was bastardised by the states that succeeded in emasculating the local governments under their absolute personal control. The local council polls usually turned into a charade that is perpetuated by charlatans in the name of elections where in reality, forceful imposition, selection and subversion of the process became the order of the day. The study examined how the use of SIECs aided the phenomenon of electoral fraud at the grassroots level where the local council elections are designed and arrested by state governors based on their selfish desire. The study utilized both primary and secondary sources of data. The data obtained were analyzed and interpreted using a mixed method of statistical tools and content analysis. The study discovered that the SIECs became tools in the pawn of the state governors that they leveraged in manipulating the local government elections against the will of the electorates at the grassroots and that has tremendously affected the democratization process in the country where authentic institutional building remains a mirage even after more than 20 years of the democratic experiment. The study recommends that the SIECs should be abrogated and the INEC should conduct the local council elections together with the national elections at the same time.